Smart factory adoption in small and medium-sized enterprises: Empirical evidence of manufacturing industry in Korea - Won, Jeong Yeon; Park, Min Jae (Technological Forecasting and Social Change, 2020)
This paper examines the factors and effects of smart factory adoption of Small and Medium-sized Enterprises (SMEs). With the emergence of the 4th industrial revolution, the use of information technologies has been gradually emphasized in order to improve the company's competence in manufacturing. Moreover, observations from various cases of government support and academic research have reportedly been stressing the impact of the information technologies on the economy. But there is little research about the adoption intentions and implementation for the SMEs. An analysis of the 2012 SMEs in Korea shows that the experienced benefits of prior information and the unique characteristics of SMEs do not have a significant influence on the adoption intention of smart factory. On the contrary, the existing information investments and efforts appear to create a large amount of resistance. This study aims to help executives and policymakers make the right decisions by understanding the meaning of smart factories as well as the conditions and impact of innovations that affect SMEs.
Keywords: Academic research; Adoption intention; Government supports; Industrial revolutions; Information investments; Manufacturing industries; Prior information; Small and medium-sized enterprise; Adoption and implementation; Determinants of technology innovation; Logistic regression; Smart factory; SMEs